The Implementation of The Concept of Value for Money in the Realization of Budget Accountability at the Regional Financial and Asset Management Agency (BPKAD) of Banjar Regency - Waspini Waspini; Nur Astri Sari; Syaiful Hifni; Novika Rosari (AFEBI Accounting Review, 2022)
This research aimed to determine the implementation of the concept of Value for Money in the realization of budget accountability at the Regional Financial and Asset Management Agency (BPKAD) of Banjar Regency. This research was qualitative research with the object studied was data on the realization of performance and financial achievements contained in the Report of Government Agency’s Performance Accountability (LAKIP) of the Regional Financial and Asset Management (BPKAD) of Banjar Regency during 2016-2019. The data analysis technique was Qualitative Descriptive based on three elements in the concept of Value for Money such as economic, efficiency and effectiveness. The results indicated that the financial management and regional assets at BPKAD of Banjar Regency were considered to be able to realize the budget accountability because, in terms of budget management, it was economical and efficient even though it did not meet the effective criteria because it had not been able to achieve the targets set. During the 2016-2019 budget year obtained an economic ratio test of 80.73% with economic criteria while for efficiency test obtained a ratio of 116.29% with efficient criteria. In addition, the effectiveness test obtained a ratio of 85.06% with ineffective criteria.